(untitled) (Journal of Music Research Online, 2022)
Australian opera in the 1990s was characterised by an overt interest in telling and retelling the stories of Australia’s immediate past. From the building of the Sydney Opera House to the trial of Lindy Chamberlain, numerous operas from this period explicitly engaged in social discourse designed to challenge prevailing notions of Australian cultural identity. Conversely, in the first decade of the twenty-first century, Australian opera has increasingly employed classical myth and European literature as the impetus for libretto and plot, eschewing an overt focus on Australian cultural material. This article examines the Australian operatic repertoire of the period and, through case studies focussing on various operas, explores the changing modes of social commentary embodied within the repertoire. Through an examination of actual operas and the commentary surrounding Australian opera, this paper posits that, while the repertoire is marked by diverse approaches to music style and idiom, it is nevertheless united by either overt or covert interactions with contemporary Australian social discourse.